Las actividades lúdicas que utilizan los docentes en el proceso enseñanza aprendizaje de la matemática en los estudiantes del segundo y tercer grados del subnivel básico elemental, de la escuela “Fiscal Mixta Lauro Damerval Ayora” nº2, del barrio La Tebaida, parroquia San Sebastián cantón y provincia de Loja, año lectivo 2012- 2013 - Maldonado Sánchez, Diego Fernando (2014)
This research work has as main objective to contribute to the recreational activities that must be implemented by teachers for the development of logical-mathematical reasoning in children of 2nd and 3rd degrees, the "Joint Fiscal Lauro Damerval Ayora" School No. 2, investigative purpose to be carried out through the implementation of three specific aims and approach, explanation, comparison and verification of the respective hypothesis. The process was carried out, after having established the research problem was to select, organize and clarify the relevant information on the implementation of activities, for which the theoretical references found, were oriented in designing a model of a guide observation aimed at teachers as for the students. The work is very important because through the application of these research techniques, it was found as the main indicator of the problems that teachers on the limited use of recreational activities in the learning of mathematics learners so I think that will be an asset for teachers, as it will serve as a guide for the use and application and appropriate and timely manner, the process of learning with the use of recreational activities in the area of math-oriented capacity building, abilities, skills and activities where the teacher is a real counselor guide conducive basic skills through playful games in the area of mathematics. Through the game, students discover as well reflect conflict and the relationships with adults, For this reason a permanent teacher training, which allows the initiative and creativity, discarding traditional schemes and proposing will require a true cognitive construction through proper application of recreational activities.